Correspondence of Maximum and Typical Performance Measures of Cognitive Processing. (June 2020) - Charek, Daniel B.; Meyer, Gregory J.; Mihura, Joni L.; O'Gorman, Emily T.
We examined associations among cognitive processing measures that varied on a continuum from maximum to typical performance tasks in the context of an ego depletion study. Our intent was to replicate and extend the findings of Charek, Meyer, and Mihura, which showed that ego depletion had an expected effect on selected scores from the Rorschach inkblot task. We hypothesized that Rorschach variables indicative of cognitive sophistication would correlate with neuropsychological measures of cognitive ability and that Rorschach variables theoretically unassociated with cognitive processing would not correlate with those criterion measures. These hypotheses were supported, providing evidence of convergent and discriminant validity. We also hypothesized ego depletion effects on all measures; however, none were evident. Methodological considerations and implications of the findings are discussed.